Chicanx histories of the present: a praxis against gang injunctions in Orange County, California, 2008–2016. (10th September 2021) - Spady, James O'Neil; Scott, Alexander; Luévano, Susan C.; Hernandez, Gabriela; Torres, Carolyn
Abstract : Chicanxs Unidxs de Orange County (CU) is a community organisation in Southern California. Founded in 2006, CU is small, multigenerational and multi-ethnic. Its organising has focused predominantly on building community power by focusing on local politics, abusive policing and the gentrification of Chicanx neighbourhoods. This article presents an evidence-based narrative of several CU campaigns (primarily between 2008 and 2016). CU's tactical aggressiveness and strategic pragmatism forced significant changes to 'civil gang injunctions' in California. For decades, California law enforcement has used such injunctions to suppress a generation of young people of colour as 'gang members'. Minors and adults have been prohibited indefinitely from engaging in otherwise legal activities without due process. CU's emphasis on the longevity of institutionalised and societal racism, rooted in the colonial conquest, resembles arguments associated with critical race theory (CRT) – though CU was not inspired by CRT. CU's praxis resembles practices of critical pedagogy – though it was not directly modelled on it either. Rather, we argue that CU's praxis is embedded in the members' lived experience and study of the local history of racism, community and social movements. All five of this article's authors were members of CU and were involved in the organising described in this article. The authors wrote this at the request of the CU membership, and it has been discussed and revised by the full membership.